Long-Time Behavior of Nonautonomous Fokker-Planck Equations and Cooling of Granular Gases - Lods, B.; Toscani, G. (Український математичний журнал, 2005)
We analyze the asymptotic behavior of linear Fokker-Planck equations with time-dependent coefficients. Relaxation towards a Maxwellian distribution with time-dependent temperature is shown under explicitly computable conditions. We apply this result to the study of Brownian motion in granular gases by showing that the Homogenous Cooling State attracts any solution at an algebraic rate. Проаналізовано асимптотичну поведінку лінійних рівнянь Фоккера - Планка з коефіцієнтами, залежними від часу. Показано, що за явно обчислюваних умов відбувається релаксація до розподілу Максвелла з залежною від часу температурою. Цей результат застосовано до вивчення броунівського руху в гранульованих газах і показано, що однорідний охолоджуючий стан притягує будь-який розв'язок з алгебраїчною швидкістю.